Radiopharmaceuticals Current Research for Better Diagnosis and Therapy - Badria, Farid A. (IntechOpen, 2022)
Radiopharmaceuticals - Current Research for Better Diagnosis and Therapy discusses the importance of radiopharmaceuticals and their environmental, pharmaceutical, diagnostic, therapeutic, and research applications. Chapters address such topics as the fundamentals of radiopharmaceutical chemistry and preparation, fabrication, materials manipulation, and characterization of radiopharmaceuticals, applications of radiopharmaceuticals in preclinical studies, radiopharmaceuticals in modern cancer therapy, and new trends in preparation, biodistribution, and pharmacokinetics of radiopharmaceuticals in diagnosis and research.